Modelling, Stability Analysis, and Control of a Buck Converter: Digital Simulation of Buck Regulator Systems in MATLAB? - George M.; Pasupuleti J. (CRC Press, 2025)
A generalized approach in a systematic way is inevitable to oversee the challenges one may face in the product development stage to acquire the desired output performance under various operating conditions. This book, Modelling, Stability Analysis, and Control of a Buck Converter: Digital Simulation of Buck Regulator Systems in MATLAB?, written and structured to cater to readers of different levels, aims to provide a clear understanding of different aspects of modelling and practical implementation. The operation of the semiconductor switches, switching characteristics of the energy storage elements, stability analysis, state-space approach, transfer function modelling, mathematical modelling, and closed loop control of the buck converter, which are illustrated in this book can be extended to any other similar system independent of complexity. This book: ? Covers modelling and control of buck converters and provides sufficient understanding to model and control complex systems ? Discusses step response, pole-zero maps, Bode and root locus plots for stability analysis, and design of the controller ? Explains time response, frequency response, and stability analysis of the resistive-capacitive (R-C), resistive-inductive (R-L), and R-L-C circuits to support the design of the buck converter ? Includes simulation and experimental results to demonstrate the effectiveness of closed loop buck regulator systems using proportional (P), integral (I), and P-I controllers to achieve the desired output performance ? Provides MATLAB codes, Algorithms, and MATLAB/PSB models to help readers with digital simulation It is primarily written for senior undergraduate and graduate students, academic researchers, and specialists in the field of electrical and electronics engineering. ? 2025 Moleykutty George and Jagadeesh Pasupuleti.